A soluble cryogenic thermometer with high sensitivity based on excited-state configuration transformations. Issue 41 (2nd October 2015) - Chen, Jianwei; Wu, Yishi; Wang, Xuedong; Yu, Zhenyi; Tian, He; Yao, Jiannian; Fu, Hongbing
Abstract : The mechanism for the dual emission of FIPAC was investigated in detail and the dual emission character of the FIPAC solution system was further applied as a cryogenic thermometer. Abstract : Cryogenic temperature detection plays an irreplaceable role in exploring nature. Developing high sensitivity, accurate, observable and convenient measurements of cryogenic temperature is not only a challenge but also an opportunity for the thermometer field. The small molecule 9-(9, 9-dimethyl-9 H -fluoren-3yl)-14-phenyl-9, 14-dihydrodibenzo[ a, c ]phenazine (FIPAC) in 2-methyl-tetrahydrofuran (MeTHF) solution is utilized for the detection of cryogenic temperature with a wide range from 138 K to 343 K. This system possesses significantly high sensitivity at low temperature, which reaches as high as 19.4% K −1 at 138 K. The temperature-dependent ratio of the dual emission intensity can be fitted as a single-exponential curve as a function of temperature. This single-exponential curve can be explained by the mechanism that the dual emission feature of FIPAC results from the excited-state configuration transformations upon heating or cooling, which is very different from the previously reported mechanisms. Here, our work gives an overall interpretation for this mechanism. Therefore, application of FIPAC as a cryogenic thermometer is experimentally and theoretically feasible.